2020
DOI: 10.1088/1755-1315/573/1/012009
|View full text |Cite
|
Sign up to set email alerts
|

Effective Implementation of low thermal conductivity material Yttrium Stabilized Zirconium Coating on a Diesel Engine Components Fuelled with neat Waste Cooking Oil-An Assessment Study

Abstract: In this study, an attempt was made on the consumption of neat waste cooking oil (WCO) in a thermal barrier coated (TBC) diesel engine. During the first stage of the study, the standard engine fuelled with diesel and WCO with different power outputs (25%, 50%, 75% & 100%) to measure the performance, combustion and emission parameters. In the second stage of the study, the engine components coated with 8% yttrium stabilized zirconium (8%YSZ) ceramic coat and NiCrAl bond coat using plasma spray coating. In th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…The comparison of mass fraction of NOx is in line with earlier work. For example, Sangeethkumar et al (2020) obtained 130 ppm, and YILMAZ (2019) reported 140 ppm. There are two peaks in the CAD range of 715°-740°,; one peak (local maximum temperature) is due to compression of air and the other is the result of combustion (fuel-air reaction).…”
Section: Simulation Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The comparison of mass fraction of NOx is in line with earlier work. For example, Sangeethkumar et al (2020) obtained 130 ppm, and YILMAZ (2019) reported 140 ppm. There are two peaks in the CAD range of 715°-740°,; one peak (local maximum temperature) is due to compression of air and the other is the result of combustion (fuel-air reaction).…”
Section: Simulation Resultsmentioning
confidence: 99%
“…The comparison of mass fraction of NOx is in line with earlier work. For example, Sangeethkumar et al (2020) obtained 130 ppm, and YILMAZ (2019) reported 140 ppm.…”
Section: Resultsmentioning
confidence: 99%